Estimation of Stature from Length and Breadth of Left Thumb in Medical Students of a Medical College in Kathmandu, Nepal (Nepal Medical College Journal, 2021)
There is enormous importance of identification for forensic experts. Identification of human remains is always challenging for them, worldwide. An individual’s parameter has been an intrinsic representative among the other parameters. To specify the relationship between height and finger length in healthy persons, both male and female, an effort has been made to originate the regression formula. A descriptive and cross-sectional study was conducted at Department of Forensic Medicine, Nepal Medical College Teaching Hospital, Kathmandu with sample size 100 males and 100 females of 18-25 years of age. The stature of male subjects was 170.02 cm mean value with SD (± 6.40). The minimum stature observed was 152.5 cm while maximum was 188 cm. In males, mean of the left thumb length was 3.2 cm with SD (±0.38). Also, breadth of the left thumb showed a mean value of 2.52cm SD (±0.46) with Pearson coefficient (0.258). By means of linear regression analysis a constant (147.096) and Pearson correlation coefficient (0.337) were obtained for the length of left thumb. In female subjects, stature was found to be 157.76 cm mean value with SD (± 6.30). The minimum stature was 136.00 cm and maximum was 175.00 cm. The mean of left thumb length was 2.95 cm and 2.25 cm for breadth with SD (±0.4166) for both. Applying multiple regression, a constant (148.83) and Pearson coefficient (0.25) were obtained for left thumb length and SD (±0.423) was obtained for left thumb breadth. In males the stature can be estimated using standard equation (S= 150.49+4.65LTL+1.82LTB). In females, stature can be estimated using standard equation (S=148.83+4.4114LTL+1.423LTB), where S=stature, LTL= left thumb length, LTB= left thumb breadth. A multiple regression equation derived by our study can be used for estimation of height in Nepalese population. If either of the measurements (left thumb length and breadth) is known, the other can be calculated. It is remarked that length and breadth of left thumb shows positive relationship with the stature.